Effect of temperature and water supply on the growth of wheat and barley in Diyala and Maysan - Muhammad Alwan, Sundus; Nasser Abbas, Kawther (Journal of College of Education, 2020)
Increasing temperature and decreasing rainfall likely have an effect on production of wheat and barley in Iraq (Diyala Province, Maysan Province). This study aims to identify the effects of spatial and climate changes on the growth of these crops in the selected areas.The wheat and barley crops are considered one of the most important field crops, and there is ability to expand their cultivation in the two governorates. There is a great opportunity to increase the yield by solving problems such salinity by using improved seeds, which is available in the two governorates.  The study clarified that the climatic requirements of each crop under study from the temperatures and rain and its effect on the cultivation and production of those crops. Results showed that temperature was suitable for production of wheat and barley while rain was inadequate in which the deficiency is compensated by irrigation.